THE EFFECT OF ADDITION BY BUTHYLATED HYDROXYTOLUENE (BHT) ON PHYSICAL PROPERTIES OF GEOMEMBRANE FROM RECYCLED HIGH DENSTY POLYETHYLENE (HFPE) PLASTIC WASTE - Veren Fransiska; Intan Syahbanu; Adhitiyawarman Adhitiyawarman (Indonesian Journal of Pure and Applied Chemistry, 2023)
Recycled High Density Polyethylene (HDPE) has been prepared for geomembrane construction material. The aim of this research was to study the effect of Butylated Hydroxytoluene (BHT) addition as an antioxidant on the characteristics of the resulting geomembrane. Fourier Transform Infra Red (FTIR) analysis was carried out to examine functional groups of recycled HDPE and prepared geomembranes. Mechanical properties, permeability and hydrophobicity of geomembrane were observed to determined optimum BHT addition. The results of FTIR analysis on recycled HDPE showed the presence of functional groups at wavelengths 2912 and 2847 cm-1 (C-H stretching); 1474 and 1467 cm-1 (CH2 bend); 721 cm-1 (CH2 Rock). After being formulated with other materials to obtain geomembranes, it was not found new peak indicating that the presence of BHT in geomembrane only physical interaction occurs. All of geomembranes had no permeability to water and reach 100% of hydrophobicity. The highest tensile test value was shown by geomembrane with 0,25 b/b% of BHT which about 21.235 MPa and 16.01 MPa for before and after soil burial test for four weeks, respectively. Perhaps might be due to the interaction between BHT at low concentrations which has lower polarity and HDPE which is nonpolar has better compatibility than at other concentrations